METODE PEMBELAJARAN DALAM MENGEMBANGKAN INTERAKSI SOSIAL ANAK TUNARUNGU - Bonifasia Ayulianti Tat; Robertus Hudin; Mikael Nardi (Jurnal Literasi Pendidikan Dasar (JLPD), 2021)
The purpose of this paper is to be describe learning methods that can develop the social interaction of children with hearing impairment. The method used was library research, where the authors analyzed the theories and research results from scientific journals, theses and dissertations related to this subject. The results showed that learning methods that can develop deaf children's social interactions are; 1) oral method. This method is very suitable to be applied to deaf children at the level of slight losses (20-30 Deci-Bell), mild losses (30-40 dB) and moderate losses (40-60 dB); 2) method of reading speech. This method is good for use at all levels of hearing loss; 3) manual method. This method is useful if it was focused on deaf children at the server level (60-75 dB) and deep losses (75 dB and above); 4) total communication method. This method can be implemented for all levels of hearing loss.